Re-Visioning Psychology in the Writing Class - Dennis Young (Journal of the Assembly for Expanded Perspectives on Learning, 1996)
With its emphasis on soul-work and the imaginal frames of psyche, archetypal psychology helps teachers more fully interpret the motivations and intricacies of writing and learning.